2013
DOI: 10.1182/blood.v122.21.493.493
|View full text |Cite
|
Sign up to set email alerts
|

The ATRA Question In AML: Lack Of Benefit Overall Or In Any Molecular Subgroup In The NCRI AML16 Trial

Abstract: Background There is conflicting data on the effect of the addition of ATRA to chemotherapy in AML. Two large randomised trials showed no benefit (Estey et al Blood 1999; 93, 2478 (n=215); Burnett et al. Blood 2010, 115: 9482 (n=1075)), or benefit which was limited to patients with an NPM1 mutation (n=14) when given in combination with ICE (Idarubicin/Ara-C/Etoposide) (Schlenk et al, Leukemia 2004, 18; 1798 (n=242)) but not with DA alone. In an effort to prospectively clarify if this is predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, it should be noted that limitations of this study include the small sample size (20 NPM1 ‐mutated patients with AML) and that other gene mutations, such as FLT3 ‐ITD, have not been investigated in this retrospective analysis . Overall, there is currently no consensus as to whether the addition of ATRA to chemotherapy improves the clinical outcome of NPM1 ‐mutated patients with AML (Table ) . Of note, dosing schedule and timing of ATRA administration, namely before, simultaneously or after exposure to conventional chemotherapy, may be relevant to explain discrepancies observed in different series .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, it should be noted that limitations of this study include the small sample size (20 NPM1 ‐mutated patients with AML) and that other gene mutations, such as FLT3 ‐ITD, have not been investigated in this retrospective analysis . Overall, there is currently no consensus as to whether the addition of ATRA to chemotherapy improves the clinical outcome of NPM1 ‐mutated patients with AML (Table ) . Of note, dosing schedule and timing of ATRA administration, namely before, simultaneously or after exposure to conventional chemotherapy, may be relevant to explain discrepancies observed in different series .…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, the randomized MRC AML12 trial for patients AML <60 years of age did not identify any molecular subgroup, defined by mutations in NPM1, FLT3, CEBPA genes, likely to derive a significant survival benefit from the addition of ATRA to aggressive chemotherapy . Consistently, in an analysis stratified by etoposide addition and NPM1/FLT3 mutational status, there was no significant improvement in clinical outcomes by the addition of ATRA to intensive chemotherapy for any subgroup of older patients enrolled in NCRI AML16 trial . Moreover, Nazha et al observed that the addition of ATRA to chemotherapy did not affect overall outcome of patients with AML regardless of NPM1 mutational status .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations